Análisis estadístico de las fuentes de video digitales comprimidas - Herrera García, Rodrigo Javier (Ingeniería, 1998)
This paper treats the behavior features of traffic obtained from a compressed digital video source to getting out a statistics model. Analysis over a 87 minutes duration movie was made. The information generated by a digital video source is generally variable bit rate data. To analize data, it should be considered that video systems services need to be real time processes and each picture must be presented in fixed times. The proposed model was based on the variation of bit rate over the interval of time each picture must be presente (i.e., picture rate). If we have a model that we can use to simulate a digital video source, we can simulate and analize the behavioral traffic in telecommunication digital networks.Nevertheless, a computer algorithm can be implemented.